TAX RISKS IN UKRAINE’S NATIONAL REVENUE STRATEGY - SHEVCHUK, Anton (Scientific journal «World of Finance», 2024)
Introduction. The modern development of public finances cannot proceed without a deep analysis and understanding of tax risks, which significantly influence the country’s economic security. Tax risks, encompassing a broad spectrum of economic and legal aspects, require a systematic approach to management and mitigation to ensure budgetary stability. The importance of studying tax risks is underscored not only by the need to optimize tax revenues but also by strengthening public trust in financial institutions, especially during periods of socio-economic upheaval and political uncertainty. The purpose of the article is to analyze the National Revenue Strategy of Ukraine in terms of proposed tax risk management measures and evaluate potential tax risks that may arise from the implementation of such a strategy in the fiscal policy framework. Results. The findings of the research involve developing suggestions for improving Ukraine’s National Revenue Strategy by implementing personal and departmental accountability for executing its stages and achieving strategic goals; developing strategic objectives for combating the shadow economy, increasing salaries, and enhancing administrative and criminal accountability of customs officials in the context of fighting corruption; and formulating proposals for refining the simplified tax system and the mechanism for setting corporate tax rates. These suggestions could serve as options for reducing tax risks both in the National Revenue Strategy of Ukraine up to 2030 and in the overall execution of fiscal policy. Conclusions. We emphasize the necessity of employing an integrated interdisciplinary approach in developing effective mechanisms for managing tax risks. Such an approach will facilitate the stabilization of state revenues and reduce the adverse impact of corruption and other illegal activities on the economy. Significant emphasis is placed on the need for a comprehensive strategy that incorporates legislative, administrative, and technological tools for effectively combating tax risks in the modern economic landscape.